Electric Lifeline Policy in Maine - Ballard, Steven; Faulkner, James; Morris, Charles; Nicoletti, Barbara; Townsend, Ralph (Maine Policy Review, 1993)
Concern about the impact of high energy costs on the low-income and elderly citizens underlies Maine’s so-called "electric lifeline" programs, which modify rates to assist qualified customers with their electric bills. Recently, researchers at the Margaret Chase Smith Policy Center conducted an evaluation of Central Maine Power Company’s electric lifeline policy. This article, based on the findings of that evaluation, examines the many regulatory and social issues that have surfaced during Maine’s lifeline experience.
Keywords: electric utilities; electric lifeline rates; Maine